KONSEP PENDIDIKAN ANAK USIA DINI (PAUD) PERSPEKTIF AL-QUR’AN DAN HADITS - Fauzah Nur 'Aini; Sriyono Fauzi (INOVASI : Jurnal Ilmiah Pengembangan Pendidikan, 2026)
Early Childhood Education (PAUD) is a crucial foundation for shaping children’s intellectual, spiritual, emotional, and moral development. Islam places significant emphasis on children’s education from an early age, as outlined in the teachings of the Qur’an and the hadith. This article aims to analyze the concept of ECE from the perspective of the Qur’an and hadith, including the stages of child development, educational programs, learning methods and approaches, as well as its importance in the future development of education. This study employs a literature review method, utilizing data sources consisting of the Qur’an, hadith, books, and relevant scientific journal articles. Data analysis was conducted using a constructive and interpretive approach to the various sources examined. The findings indicate that the concept of ECE in Islam begins from the prenatal phase through childhood through the instillation of faith, the cultivation of worship, the development of character, compassion, and exemplary behavior. The Qur’an and hadith also provide guidelines regarding educational methods such as uswah hasanah, habit formation, storytelling, targhib wa tarhib, and a holistic approach to child development. Furthermore, early childhood education in Islam holds high urgency as the foundation for character formation and a civilizational investment in fostering a generation that is faithful, morally upright, and knowledgeable.